Coordination-Directed Self-Assembly of Functional Polynuclear Lanthanide Supramolecular Architectures - Li, Xiao-Zhen; Tian, Chong-Bin; Sun, Qing-Fu (Chemical reviews, 2022)
Lanthanide supramolecular chemistry is a fast growing and intriguing research field due to the unique photophysical, magnetic, and coordination properties of lanthanide ions (LnIII). Compared with the intensively investigated mononuclear Ln-complexes, polymetallic lanthanide supramolecular assemblies offer more structural superiority and functional advantages. In recent decades, significant progress has been made in polynuclear lanthanide supramolecules, varying from structural evolution to luminescent and magnetic functional materials. This review summarizes the design principles in ligand-induced coordination-driven self-assembly of polynuclear Ln-structures and intends to offer guidance for the construction of more elegant Ln-based architectures and optimization of their functional performances. Design principles concerning the water solubility and chirality of the lanthanide-organic assemblies that are vital in extending their applications are emphasized. The strategies for improving the luminescent properties and the applications in up-conversion, host–guest chemistry, luminescent sensing, and catalysis have been summarized. Magnetic materials based on supramolecular assembled lanthanide architectures are given in an individual section and are classified based on their structural features. Challenges remaining and perspective directions in this field are also briefly discussed.